DESIGN OF EXPERT-BASED ECO-FRIENDLY RP-HPLC ANALYTICAL METHOD FOR THE ESTIMATION OF LUMEFANTRINE FROM THE CARBON DOTS - RAKSHA; GUPTA, ASHUTOSH; SAHA, MOUMITA; MOORKOTH, SUDHEER; BHARDWAJ, ABHAY; RAJORA, ADITYA DEV (International Journal of Applied Pharmaceutics, 2026)
Objective: The most common and lethal malaria-causing species in humans, Plasmodium falciparum and Plasmodium vivax, are caused by protozoan parasites belonging to the genus Plasmodium. Due to the substantial therapeutic obstacles posed by these parasites, novel therapy strategies are being investigated. By improving the solubility and cellular absorption of antimalarial drugs, including lumefantrine (LUM), carbon dots (CDs), a new nanomaterial, hold promise for the management of malaria. In order to evaluate the stability, drug release profile, and percentage entrapment efficiency (%EE) of LUM-loaded CDs and support their potential for the treatment of malaria, this study set out to design and validate an analytical approach based on HPLC. Methods: A Design of Experiments (DoE) strategy was employed to optimize the HPLC process, systematically altering the injection volume, flow rate, buffer ratio, and buffer pH to improve performance. The following responses were tracked: theoretical plates (Tp), tailing factor (Tf), drug peak area, and retention time (RT). Following the requirements of ICH Q2(R2), linearity was established for LUM throughout a range of 0.5 to 20 µg/ml. Results: The result was a linear regression equation with an R2>0.999, demonstrating strong linearity. For both intra-day and inter-day studies, the method's precision with a %CV<2% and accuracy between 98 and 102% ensured repeatability when used for evaluating LUM stability, %EE, and drug release in CDs. The technique exhibited sensitivity for low concentrations and selectivity, separating LUM from excipients and degradation products. Its eco-friendliness was confirmed with an AGREE score of 0.7, indicating less waste and solvent consumption. Conclusion: The quantification of LUM in CDs, formulation parameter optimization, and the development of sustainable malaria treatment techniques are all made possible by this verified HPLC approach.